Factors affecting diet quality in adolescents: the effect of sociodemographic characteristics and meal consumption: FACTORS AFFECTING DIET QUALITY IN ADOLESCENTS - ATEŞ ÖZCAN, BURCU; YEŞİLKAYA, Burcu and YALDIZ, Nihan and PEHLİVAN, Merve (Progress in Nutrition, 2021)
Background: Determining the quality of diet in individuals and having a good understanding of the factors affecting it would be essential in understanding the means to improve diet quality. Objectives: This study aimed to determine the diet quality and the factors affecting the diet quality of middle adolescents using the Mediterranean Diet Quality Index (KIDMED). Methods: In total, 550 adolescents aged 14–18 years participated in the study. Individuals who voluntarily participated completed the KIDMED scale and a questionnaire that investigated the demographic and general characteristics, eating habits, and anthropometric measurements. Of the participants, 57.5% were girls and 42.5% were boys. The mean KIDMED score of the participants was 5.12 ± 2.40. A model was created based on age, sex, number of main meals and snacks, BMI, income level, and education level of the parents, which were considered to have an effect on KIDMED. Increase in the BMI increased the KIDMED score by 0.057 units; additionally, the score increased in women by 0.550 units, in individuals with an income that was higher than their expenses by 1.245 units, in cases when the participant’s mother had a graduate-level education by 1.541 units, and in cases when the participant’s father had a high school diploma level education by 0.621 units. In total, 75.2% of the KIDMED score was explained through these variables. Results: According to the study data, diet quality of the adolescents was at a medium level, and diet quality was affected by the family income, parental education level, gender, number of meals, and BMI. Conclusions: These results show the need for intervention programs that consider the general and sociodemographic characteristics of the individuals and their families, as well as other factors such as healthy eating habits and body weight.